Almost Nearly Quasi $(τ_1,τ_2)$-continuous Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This paper deals with the concept of almost nearly quasi $(τ_1,τ_2)$-continuous multifunctions.Moreover, several characterizations and some properties concerning almost nearly quasi $(τ_1,τ_2)$-continuousmultifunctions are considered.
Keywords: upper almost nearly quasi $(τ_1,τ_2)$-continuous multifunction; lower almost nearly quasi $(τ_1,τ_2)$-continuous multifunction; almost nearly quasi $(τ_1,τ_2)$-continuous multifunction